Avaliação experimental de tijolos ecológicos visando sua aplicação em construções sustentáveis - Silva, Jaqueline Arice Gaudencio da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The ecological brick is an interesting alternative to soften the environmental impacts generated by the construction and reduce the housing deficit, because it allows for lower costs, less material consumption and, therefore, a more sustainable construction. This work had the objective of evaluating the characteristics and properties of ecological bricks produced with three types of soil, through the physical, chemical and mineralogical characterization of soils and the mechanics of ecological bricks. In addition to the evaluation of the bricks, the work also aims to promote the use of the soil-cement technique as an alternative to sustainable construction. The results obtained evidenced the possibility of brick fabrication using the soil-cement technique, with the use of different types of soil. The bricks produced with the three evaluated soils have met most of the standards and requirements specified in the standard and can be applied to buildings that seek to meet the concept of sustainability

O tijolo ecológico constitui uma alternativa bastante interessante para amenizar os impactos ambientais gerados pela construção civil e diminuir o déficit habitacional, pois possibilita diminuição de custos, menor consumo de materiais e, portanto, uma construção mais sustentável. Este trabalho teve o objetivo de avaliar as características e propriedades de tijolos ecológicos produzidos com três tipos de solo, por meio da caracterização física, química e mineralógica dos solos e mecânica dos tijolos ecológicos. Além da avaliação dos tijolos, o trabalho também visa divulgar o emprego da técnica solo-cimento, como alternativa de construção sustentável. Os resultados obtidos evidenciaram a possibilidade da fabricação de tijolos utilizando a técnica de solo-cimento, com a utilização de diferentes tipos de solo. Os tijolos produzidos com os três solos avaliados atenderam a maioria dos padrões e requisitos especificados em norma e podem ser aplicados em construções que buscam atender ao conceito de sustentabilidade
Experimental evaluation of ecological bricks aiming their application in sustainable constructions
Keywords: Tijolos; Solo-cimento; Sustentabilidade; Construção civil; Bricks